Dysosteosclerosis is also caused by TNFRSF11A mutation - Guo, Long; Elcioglu, Nursel H.; Karalar, Ozge K.; Topkar, Mert O.; Wang, Zheng; Sakamoto, Yuma; Ikegawa, Shiro (Nature Publishing Group, 2018)
Dysosteosclerosis (DOS) is a form of sclerosing bone disease characterized by irregular osteosclerosis and platyspondyly. Its mode of inheritance is autosomal recessive. SLC29A3 mutations have been reported as the causal gene in two DOS families, however, genetic heterogeneity has been suggested. By whole-exome sequencing in a Turkish patient with DOS, we found a novel splice-site mutation in TNFRSF11A. TNFRSF11A mutations have previously been reported in two autosomal dominant diseases (osteolysis, familial expansile and Paget disease of bone 2, early-onset) and an autosomal recessive disease (osteopetrosis, autosomal recessive 7). The biallelic mutation, c. 616+3A>G, identified in our study was located in the splice donor site of intron 6 of TNFRSF11A. Exon trapping assay indicated the mutation caused skipping of exon 6, which was predicted to induce a frame-shift and an early termination codon in all known alternative transcript variants of TNFRSF11A. The predicted effect of the mutation for the isoforms was different from those of the previously reported mutations, which could explain the difference of their phenotypes. Thus, our study identified the second disease gene for DOS. TNFRSF11A isoforms may have the different roles in skeletal development and metabolism.
Keywords: Metaphyseal Dysplasia; Sequencing Data; Osteopetrosis; Identification; Rank; Form